Thermal history of nakhlites: a comparison between MIL03346 and its terrestrial analogue Theo's flow - Domeneghetti MC; Fioretti AM; McCammon C; Alvaro M.; CAMARA ARTIGAS, Fernando (Copernicus Meetings, 2012)
Miller Range (MIL03346) is a nakhlite found in Antarctica [1, 2], and interpreted as an igneous cumulate erupted onto the surface of Mars [3, 4]. A single-crystal X-ray diffraction (SC-XRD) and Mössbauer spectroscopy study on the intracrystalline cation distribution of an augitic core-crystal from MIL03346 (_Wo40En36Fs24) performed by [5] clearly showed a high degree of order in the Fe2+-Mg distribution in agreement with [6] corresponding to a closure temperature Tc=500(100)°C newly calculated using the geothermometer by [7]. Because the Tc of the ordering process depends both on the kinetics of the Fe2+-Mg exchange reaction and on the cooling rate of the host rock, it allows to retrieve information on the cooling rate of the sample: lower Tc would correspond to slower cooling rate. The slow cooling rate inferred for MIL03346 is in disagreement with petrologic evidences (i.e. [1,8]) that indicate this sample to belong to a fast cooled lava flow (i.e. 3-6°C/h [1, 9]). In order to clarify this discrepancy we undertook a SC-XRD study of an augite (_Wo41En49Fs10) from a pyroxenite (TS-7, [10]) of Theo’s flow, a 120-m-thick, lava flow (Ontario, Canada, [11]) regarded as a terrestrial analogue of MIL03346 [12]. Sample TS-7 is in the middle of the pyroxenite unit, about 85m below the top of the sequence. The volcanic sequence records a very low-grade metamorphic alteration in the chlorite to prehnite-pumpellyite facies. SC-XRD data from TS-7 augite yields a Tc= 600(20)°C, consistent with the cooling rate expected at 85m below the surface. This Tc is higher, although similar within error, to the Tc=500(100)°C obtained for MIL03346 thus suggesting a relatively slower cooling for MIL03346 with respect to TS-7. This result appears inconsistent with the very shallow depths of origin (e.g. <2m) assumed for MIL03346 [13], further supporting the discrepancy between MIL03346 textural and petrologic evidences of fast cooling and the augite geothermometer results. A tentative scenario, is that, soon after eruption and initial ...